2017
DOI: 10.1186/s13756-017-0222-z
|View full text |Cite
|
Sign up to set email alerts
|

High burden of antimicrobial resistance among gram negative bacteria causing healthcare associated infections in a critical care unit of Nepal

Abstract: Background: Healthcare associated infections (HCAI) and antimicrobial resistance are principal threats to the patients of intensive care units and are the major determining factors for patient outcome. They are associated with increased morbidity, mortality, excess hospitalization and financial costs. The present study is an attempt to investigate the spectrum and antimicrobial resistance of bacterial isolates involved in healthcare associated infections (HCAI) in the patients of a critical care unit at a tert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

31
99
6
9

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(145 citation statements)
references
References 44 publications
31
99
6
9
Order By: Relevance
“…This is comparable with the study [19,20,21]. Reasons for such alarming MDR might be inappropriate and incorrect administration of antimicrobial agents as empirical treatment and lack of appropriate infection control strategies, which can cause a shift to increase prevalence of resistant organism in the community [22][23][24][25].…”
Section: Discussionsupporting
confidence: 68%
“…This is comparable with the study [19,20,21]. Reasons for such alarming MDR might be inappropriate and incorrect administration of antimicrobial agents as empirical treatment and lack of appropriate infection control strategies, which can cause a shift to increase prevalence of resistant organism in the community [22][23][24][25].…”
Section: Discussionsupporting
confidence: 68%
“…Parajuli et al, from Kathmandu, Nepal, reported Acinetobacter as the most common pathogens from ICU patients followed by Klebsiella, E coli and Pseudomonas species. 21 Study from Bangladesh reported Klebsiella pneumoniae as most common bacterial pathogens from lower respiratory tract. 19 The spectrum of pathogens and drug resistance pattern vary from hospital to hospital, within and outside country along with type of illness among the patients.…”
Section: Discussionmentioning
confidence: 99%
“…57 In another study, Enterobacteriaceae community were found to be completely resistant to third-generation cephalosporins. 58 Over 80% of the Klebsiella spp. community were resistant to ciprofloxacin, gentamicin, piperacillin, tazobactam, and imipenem showing 48.6% resistance.…”
Section: Prevalence and Brief Outline Of Hcaismentioning
confidence: 99%
“…community were resistant to ciprofloxacin, gentamicin, piperacillin, tazobactam, and imipenem showing 48.6% resistance. E. coli was equally resistant although carbapenems were effective in almost 58 Another study reported that although the Acinetobacter spp. were 76.99%-92.01%, resistant to most antimicrobials, only 30% of Acinetobacter spp.…”
Section: Prevalence and Brief Outline Of Hcaismentioning
confidence: 99%